Optimalisasi Campuran Fly Ash, Bottom Ash, dan Semen Untuk Lapis Pondasi (Improving Subgrade) - Nely Mak'sudah, Ari; Adi Saputro, Yayan; Rochmanto, Decky (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2022)
PLTU Tanjung Jati B Jepara causes excessive environmental pollution, namely fly ash and bottom ash (FABA) waste. So this waste is very suitable to be used as a stabilizing mixture for ordinary embankment soil. The purpose of this study was to find the optimal value for the foundation layer, using an experimental method to examine the free compressive strength of the soil stabilizing material. By using a mixture of 50% FA + 50% BA and 60% FA + 40% BA with the percentage of cement addition of 3%,5%,7%,9%,11%,15%. The results showed that the highest stress value occurred in the mix design 50% FA+50% BA with a percentage of 9% cement, the highest stress increase was at a percentage value of 4,943 kg/cm2 during a 3 day curing period. With the highest field density value at T3 of 1,553 gr/cm3. With the results of the highest soil density R value at T3 of 123.247%. The UCS and CBR values ​​for the best comparison for the foundation layer increased with the addition of bottom ash composition and PCC content in the mixture.